Formalisasi Syariat Islam Di Tasikmalaya - Anang Zubaidy (Jurnal Hukum IUS QUIA IUSTUM, 2008)
Together with the occurrence of democracy in Indonesia through reformation in 1998, the practice on state administration is in dynamic way. One of the dynamics is the existence of the regional autonomy whose implementation triggered a wide interpretation among society. One of the pros and cons around regional autonomy is the existence of shariah regional regulation in some places in Indonesia; one of them is in Tasikmalaya regency. Those who agree on this regulation based themselves on regional autonomy. Meanwhile, the ones who against the regulation have argument on the basis that religion business is on the hand of a central authority which is not given as a part of the autonomy